High Risk for HIV following Syphilis Diagnosis among Men in Florida, 2000–2011. (March 2014) - Peterman, Thomas A.; Newman, Daniel R.; Maddox, Lorene; Schmitt, Karla; Shiver, Stacy
Objective: Multiple interventions have been shown to reduce the risk of HIV acquisition, including preexposure prophylaxis with antiretroviral medications, but high costs require targeting interventions to people at the highest risk. We identified the risk of HIV following a syphilis diagnosis for men in Florida. Methods: We analyzed surveillance records of 13- to 59-year-old men in Florida who were reported as having syphilis from January 1, 2000, to December 31, 2009. We excluded men who had HIV infection reported before their syphilis diagnosis (and within 60 days after), then searched the database to see if the remaining men were reported as having HIV infection by December 31, 2011. Results: Of the 9, 512 men with syphilis we followed, 1, 323 were subsequently diagnosed as having HIV infection 60–3, 753 days after their syphilis diagnosis. The risk of a subsequent diagnosis of HIV infection was 3.6% in the first year after syphilis was diagnosed and reached 17.5% 10 years after a syphilis diagnosis. The risk of HIV was higher for non-Hispanic white men (3.4% per year) than for non-Hispanic black men (1.8% per year). The likelihood of developing HIV was slightly lower for men diagnosed with syphilis in 2000 and 2001 compared with subsequent years. Of men diagnosed with syphilis in 2003, 21.5% were reported as having a new HIV diagnosis by December 31, 2011. Conclusion: Men who acquire syphilis are at very high risk of HIV infection.